IMPLEMENTATION OF SCOUT EKTRACURICULAR IN FORMING THE DISCIPLINE CHARACTER OF SDN MAGUWOHARJO 1 YOGYAKARTA - Fikriyah, Siti Nur; Sutilah, Dewi (Sunan Kalijaga International Journal on Islamic Educational Research, 2022)
School is an educational institution that is responsible for providing various knowledge and skills, as well as developing various values ​​and attitudes, both through formal and non-formal education. To instill discipline, it seems that it is not enough to just rely on the learning process in class. Therefore there must be a companion program to achieve it. One of the companion programs that can be developed is with scout extracurricular activities. Scouts build good morals for the nation's children. Through scout education, it is possible to develop piety to God Almighty, national and state life based on Pancasila, pre-defence state education, personality and noble character. This study aims to analyze the problem of implementing scout extracurriculars in the formation of the disciplinary character of SDN Maguwoharjo 1 Yogyakarta and how the implementation of scout extracurricular activities at SDN Maguwoharjo 1 Yogyakarta. The research method used is descriptive qualitative by describing phenomena that occur in the field naturally and not under controlled conditions. Data collection techniques using observation and interviews. Data analysis uses the theory of Miles and Huberman, which includes data reduction, data display, and conclusion and verification. The results showed that scout extracurriculars were able to have positive implications and become a forum for students of SDN Maguwoharjo 1 Yogyakarta in developing their skills.